Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.ultsonch.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted enhancement in natural dye extraction from beetroot for industrial applications and natural dyeing of leather

Abstract: There is a growing demand for eco-friendly/non-toxic colorants, specifically for health sensitive applications such as coloration of food and dyeing of child textile/leather garments. Recently, dyes derived from natural sources for these applications have emerged as an important alternative to potentially harmful synthetic dyes and pose need for suitable effective extraction methodologies. The present paper focus on the influence of process parameters for ultrasound assisted leaching of coloring matter from pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(107 citation statements)
references
References 16 publications
3
87
0
8
Order By: Relevance
“…This increase could be because of rupturing the membrane of anthocyanoplasts by ultrasonic waves and simple release of anthocyanins, while with regard to water bath method, anthocyanins might be discharged through the concentration gradient. Sivakumar et al (2009) demonstrated a significant increase in betalains (red coloured cyanins) extraction from beetroot in comparison with the magnet stirrer extraction method. According to Table 2, the minimum response i.e.…”
Section: Resultsmentioning
confidence: 97%
“…This increase could be because of rupturing the membrane of anthocyanoplasts by ultrasonic waves and simple release of anthocyanins, while with regard to water bath method, anthocyanins might be discharged through the concentration gradient. Sivakumar et al (2009) demonstrated a significant increase in betalains (red coloured cyanins) extraction from beetroot in comparison with the magnet stirrer extraction method. According to Table 2, the minimum response i.e.…”
Section: Resultsmentioning
confidence: 97%
“…Junqueira-Goncalves et al 2011, investigated the beetroot extract as a colorant for cream cheese, they reported that beetroot extracts might be a potential alternative dye for food. Sivakumar et al 2009, has been studied on the use of power ultrasound to improve the extraction of beetroot dye and application to the substrates such as leather and they reported that the beetroot is suitable for dying leather.…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
“…As the ultrasonic intensity is further increased the cavitation effect starts decreasing and thermal effect becomes predominated. Sivakumar et al (2009) worked on ultrasonic extraction of natural dye from beetroot. In that study although the maximum extraction yield was reached at 100 W ultrasonic power, they recommended 80 W power application because the excessive energy dissipation in the form of heat when 100 W was applied.…”
Section: Conventional Organic Solvent Extraction (Cose)mentioning
confidence: 99%
“…Implosions of cavitation bubbles generate high pressure and temperature and enough to obtain sufficient reaction energy (Vinatoru 2001;Khan et al 2010). Some recent studies shows that ultrasound assisted application accelerates extraction rate and increase the yield about 10 % (Khan et al 2010, Sivakumar et al 2009Xu 2008).…”
Section: Introductionmentioning
confidence: 99%